Definición y caracterización de las cerámicas a mano con decoración pintada del sur de la península ibérica en época tartésica - Miguel Naranjo, Pedro, (Archaeopress Archaeology, 2020)
This volume presents a study of the handmade ceramics with painted decoration from the Late Bronze Age and the First Iron Age in the Guadalquivir and Guadiana valleys - the context in which the Tartessian culture developed - defining their technical characteristics, dispersion, forms, decoration, symbolism, chronology, use and meaning.